PREGNANCY ASSOCIATED BREAST CANCER (PABC): REPORT FROM A PERIPHERAL PRIMARY SUB CENTRE IN NORTH EAST INDIA - Dr Siddhartha Buragoha; Dr. Pompi Daimari (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
BackgroundPregnancy associated breast cancer (PABC) is a rare entity and defined as breast cancer diagnosed during pregnancy or one-year post-partum. There is sparse data especially from low and middle-income countries (LMIC) and merits exploration.MethodsThe study (2015 to 2020) evaluated clinicopathological characteristics, treatment patterns and outcomes of PABC.ResultsThere were 10 patients, median age of 29.5 years; 4 had triple-negative disease, 3 had hormone-receptor (HR) positive and HER2 negative, 2 had HER2-positive and HR negative and 1 had triple positive disease. 8 had IDC grade III tumour’s and 6 had delayed diagnosis. 2 patients were EBC, 6 patients were LABC and 2 patients were MBC. Trastuzumab, tamoxifen, and radiotherapy were administered post-delivery.Of the 10 patients, 7 were diagnosed antepartum (AP) and 3 had termination, 1 had preterm and 3 had full-term deliveries(FTDs). Among 3 patients who underwent MTP 2 patients had metastatic disease and 1 patients underwent termination willingly. Among postpartum group (n= 3), all were LABC and underwent NACT.ConclusionData from the tertiary cancer centre in North east India showed that the majority had delayed diagnosis and aggressive features(TNBC, higher grade). Treatment was feasible in majority and with favourable maternal and foetal outcomes.